Roseburia species in intestinal flora in amateur and professional male football players: Roseburia Intestinal Flora football players - Çıplak, Mustafa Ertuğrul; Genç, Ayça; Bilici, Muhammet Fatih; Güder, Ferhat; Acar, Hakan; Tutkun, Erkut (Progress in Nutrition, 2020)
Background: Intestinal flora varies throughout life-long by being affected by many factors such as diet, stress, and exercise Purpose: In this study, it was aimed to examine roseburia intestinal flora in amateur and professional male football players. Materials and Methods: A total of 10 male volunteers, aged between 18-21, playing football in the professional league (n=5) and playing football in the amateur league (n=5) participated in the study. A “stool sample” was taken from all subjects and a metagenomic analysis of the Roseburia genus was performed using the IlluminaMiSeq analyzer with the Next-Generation Sequencing method. In addition, a questionnaire was applied to determine participants’ eating and nutrition habits. SPSS 20.0 package program and Minitab 17 software were used in the analysis of the data, the level of significance was taken as p